Relationship between research self-efficacy and evidence-based practice in the medical students - Zahra Zia; Alireza Salehi; Mitra Amini; Hossein Molavi Vardanjani; Malihe Sousani Tavabe (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Due to the rapid advancement of medical knowledge, promotion in research is necessary to have the best clinical practice. Research Self-efficacy (RSE) is the researcher's confidence in their ability to conduct a specific study. The Evidence-Based Practice (EBP) represents how to improve the quality of care and treatment of patients. RSE and EBP are the cornerstones of successful research and then efficacious medical practice.This study aims to evaluate RSE and acceptance of EBP and their correlation among medical students. MATERIALS AND MEHODS: This is a cross-sectional study designed on 600 clinical students at the medical school of Shiraz, using a census method in 2020. Students were invited to fill out the standardized Phillips and Russell's questionnaires about RSE (4 domains, 33 questions) and Rubin and Parrish's questionnaire of EBP (10 questions). The gathered data were analyzed through the SPSS at α = 0.05 using descriptive statistics, t-test, Chi-square, and multiple linear regressions. RESULTS: There was a positive correlation between EBP and RSE score (P < 0.05). The results of linear regression test showed that all variables had a significant effect on our response variables and their effect were significant (P < 0.05). The highest mean score in RSE was shown in the subscale of writing skills (52.54). The lowest score was observed in the subscale of quantitative (student's subjective assessment of their ability to work with statistically related data and formulas) as well as computer skills (35.61). CONCLUSIONS: Students who participated in a research project, workshop, or Master of Public Health program got a higher RSE and EBP. Due to the positive correlation between RSE and EBP, we conclude that trained physicians who can research independently and use research evidence can find the best treatment approach for patients. These finding support the importance of integrating research education in medical curriculum to increase RSE and finally improvement of EBP among medical students.